The neuroenergetics of stress hormones in the hippocampus and implications for memory - Osborne, Danielle M.; Pearson-Leary, Jiah; McNay, Ewan C. (Frontiers in Neuroscience, 2015)
Acute stress causes rapid release of norepinephrine (NE) and glucocorticoids (GCs), both of which bind to hippocampal receptors. This release continues, at varying concentrations, for several hours following the stressful event, and has powerful effects on hippocampally-dependent memory that generally promote acquisition and consolidation while impairing retrieval. Several studies have characterized the brain's energy usage both at baseline and during memory processing, but there are few data on energy requirements of memory processes under stressful conditions. Because memory is enhanced by emotional arousal such as during stress, it is likely that molecular memory processes under these conditions differ from those under non-stressful conditions that do not activate the hypothalamic-pituitary-adrenal (HPA) axis. Mobilization of peripheral and central energy stores during stress may increase hippocampal glucose metabolism that enhances salience and detail to facilitate memory enhancement. Several pathways activated by the HPA axis affect neural energy supply and metabolism, and may also prevent detrimental damage associated with chronic stress. We hypothesize that alterations in hippocampal metabolism during stress are key to understanding the effects of stress hormones on hippocampally-dependent memory formation. Second, we suggest that the effects of stress on hippocampal metabolism are bi-directional: within minutes, NE promotes glucose metabolism, while hours into the stress response GCs act to suppress metabolism. These bi-directional effects of NE and GCs on glucose metabolism may occur at least in part through direct modulation of glucose transporter-4. In contrast, chronic stress and prolonged elevation of hippocampal GCs cause chronically suppressed glucose metabolism, excitotoxicity and subsequent memory deficits.